A Pharmacovigilance Study of Hydroxychloroquine Cardiac Safety Profile: Potential Implication in COVID-19 Mitigation - Singh, Anand Prakash (J Clin Med, 2020)
In light of the favorable outcomes of few small, non-randomized clinical studies, the Food and Drug Administration (FDA) has issued an Emergency Use Authorization (EUA) to Hydroxychloroquine (HCQ) for hospitalized coronavirus disease 2019 (COVID-19) patients. In fact, subsequent clinical studies with COVID-19 and HCQ have reported limited efficacy and poor clinical benefits. Unfortunately, a robust clinical trial for its effectiveness is not feasible at this emergency. Additionally, HCQ was suspected of causing cardiovascular adverse reactions (CV-AEs), but it has never been directly investigated. The objective of this pharmacovigilance analysis was to determine and characterize HCQ-associated cardiovascular adverse events (CV-AEs). We performed a disproportionality analysis of HCQ-associated CV-AEs using the FDA adverse event reporting system (FAERS) database. The FAERS database, comprising more than 11,901,836 datasets and 10,668,655 patient records with drug-adverse reactions, was analyzed. The disproportionality analysis was used to calculate the reporting odds ratios (ROR) with 95% confidence intervals (CI) to predict HCQ-associated CV-AEs. HCQ was associated with higher reporting of right ventricular hypertrophy (ROR: 6.68; 95% CI: 4.02 to 11.17), left ventricular hypertrophy (ROR: 3.81; 95% CI: 2.57 to 5.66), diastolic dysfunction (ROR: 3.54; 95% CI: 2.19 to 5.71), pericarditis (ROR: 3.09; 95% CI: 2.27 to 4.23), torsades de pointes (TdP) (ROR: 3.05; 95% CI: 2.30 to 4.10), congestive cardiomyopathy (ROR: 2.98; 95% CI: 2.01 to 4.42), ejection fraction decreased (ROR: 2.41; 95% CI: 1.80 to 3.22), right ventricular failure (ROR: 2.40; 95% CI: 1.64 to 3.50), atrioventricular block complete (ROR: 2.30; 95% CI: 1.55 to 3.41) and QT prolongation (ROR: 2.09; 95% CI: 1.74 to 2.52). QT prolongation and TdP are most relevant to the COVID-19 treatment regimen of high doses for a comparatively short period and represent the most common HCQ-associated AEs. The patients receiving HCQ are at higher risk of various cardiac AEs, including QT prolongation and TdP. These findings highlight the urgent need for prospective, randomized, controlled studies to assess the risk/benefit ratio of HCQ in the COVID-19 setting before its widespread adoption as therapy.